The Effectiveness of Combination Online and Offline Health Promotion on Gastritis Prevention Among Undergradute Nursing Students - Tri Mochartini; Nyoman Indah Santika Dewi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Gastritis is an acute or chronic inflammation of the mucous lining of the stomach wall, and it commonly affects students with a heavy lecture load. The purpose of this study was to determine the effectiveness of a combination of online and offline health promotion on the prevention of gastritis in nursing undergraduate students. Methods: This study examines the efficacy of health promotion using magnification media and leaflets for the prevention of gastritis. It employs the Cross Sectional method to assess independent and dependent variables. Using a random sample of 176 first-year students, 153 samples were divided into two groups: magnification and leaflet media. Normality tests and paired T tests are utilized to determine the impact of independent variables. Results: Show of Bivariate Analysis with Paired T Test with a sample of 153 respondents (N = 153) obtained data that T - count (21.345), T - Table (0.662) and the p.Value is (0.004) alpha value (0.05) which means there is a difference in the initial level students of Stikes Abdi Nusantara about preventing gastritis after being given education through zoom media and leaflets. Conclusions: Based on the result that 121 students had a good diet, while 21% had an adequate diet. Gastritis, caused by improper dietary habits, is more common among women. Stress levels were found to be a significant factor in gastritis incidence. Education through Zoom media and leaflets significantly improved initial-year students' knowledge of gastritis prevention.